(3JYdjb Ydi Gdbhd GdLdi aj JQLeI GHf JjejI GdMfHdis - (3eMeO GdJGadGJis; (3eMeO Hf eMeO GdHNGQj GdGKQj GdMfajs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd CFeI GdgOi GdCNHGQ UjGQaI GdCKQ hQLGdg s
(3BNQgG (B:s
(3heG PGc EdG dbUhQ CUMGH Gdgee EdG GdfGOQ , hbdjd eGge ai gPG GdReGf GdOGKQ hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGef YTQs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ GSMGb ehSi GdMSjfi GdNdGUI s
Keywords: (3Gdabg GdTGaYjs